The Effectiveness of Posters as A Media for Monitoring and Stimulation of Children's Growth and Development - Lulianthy, Eliyana; Aprina, Tilawaty; Putri, Dwi Khalisa; Purnamasari, Intan (Jurnal Kebidanan, 2023)
Disorders of child growth and development have an impact on morbidity throughout the child's life cycle, transmission of poverty between generations and long-term effects that can hinder the pace of development of a country. Nevertheless, as recorded in the 2018 Early Childhood Development Index, more than 95% of early childhood children in Indonesia have physical and learning abilities that are appropriate for their age and stage of development. However, the development of numeracy literacy and emotional social skills are still below 70%. Thereby, knowledge, attitudes and behavior of parents were correlated with the level of stimulation of growth and development in children. Therefore, this mixed method pre-experimental study aimed to investigate the effectiveness of the "Healthy Child Poster" on the knowledge, attitudes and behavior of parents in monitoring and stimulating children's growth and development. One-Group Pretest-Posttest design was applied to test the sample determined by the Accidental Sampling technique following the specified inclusion criteria. The results showed an increase in the average values of knowledge, attitudes and behavior of mothers in monitoring child growth and development after being given healthy child posters. In addition, the mothers interviewed in this study found that the posters hung on the walls of their homes were always visible and reminding, thus helping them to easily understand the messages conveyed. Therefore, promotive and preventive strategies in monitoring and stimulating children's growth and development need to be improved to strengthen the knowledge, attitudes and behavior changes of parents.